Exploring the Effectiveness of PjBL in Enhancing Students' Understanding of Astronomy Concepts Using Universe Sandbox - Kusumaningrum, Sabrina Ratih; Khamdun, Khamdun; Riswari, Lovika Ardana (Mimbar Sekolah Dasar, 2025)
Challenges in elementary education frequently arise from the continued use of conventional and monotonous teaching methods, which often lead to low student engagement and difficulty in grasping abstract concepts such as astronomy. These issues are further compounded by the limited availability of digital learning tools and insufficient teacher training. The gap between the expected implementation of interactive learning and actual classroom practices highlights the urgent need for innovative approaches. One such approach is PjBL integrated with interactive media to improve students' conceptual understanding. This study aims to (1) analyze students’ conceptual understanding of astronomy before and after instructional intervention, and (2) measure the extent of improvement achieved through the implementation of PjBL supported by Universe Sandbox media. Employing a quasi-experimental design (one-group pretest-posttest) involving 32 sixth-grade students at SDN 7 Gondosari, data were collected using tests, observations, interviews, and documentation. The data were analyzed through normality testing, paired sample t-tests, and N-Gain calculations. The results indicated a statistically significant difference between pretest and posttest scores, with the paired sample t-test yielding a Sig. (2-tailed) value of 0.000 (0.05), suggesting a substantial increase in conceptual understanding. Additionally, the N-Gain analysis produced an average score of 0.7486, categorized as moderate to high improvement. These findings confirm that the PjBL model, when supported by Universe Sandbox media, is effective in enhancing students’ comprehension of astronomical concepts.